INTRINSIC ELEMENT TRANSFORMATION FAIRY TALE INTO FILM: ECRANIZATION OF SNOW WHITE FAIRY TALE (1812) INTO SNOW WHITE AND THE HUNTSMAN FILM (2012) - Rahmat Fajar (English Literature Department, Adab and Humanities Faculty, 2025)
This study explores the transformation of the Snow White fairy tale (1812) by the Brothers Grimm into the film Snow White and the Huntsman (2012) through the lens of ecranization. The research focuses on how intrinsic elements—such as theme, plot, characters, setting, and moral values—are adapted to suit cinematic conventions and contemporary cultural values. Using a qualitative descriptive method and a comparative literature approach, the analysis applies Eneste’s theory of ecranization to identify elements of reduction, addition, and variation in the adaptation process. The findings reveal significant changes, including Snow White’s reimagining as a strong female leader and the addition of new characters and political themes. The film departs from the original’s moral simplicity to embrace more complex messages of resistance, leadership, and justice. This study concludes that adaptation serves not only as a medium shift but also as a reinterpretation shaped by modern audiences expectations